2010
DOI: 10.3174/ajnr.a2295
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Initial Experience of a Multisection Balanced Steady-State Free Precession Cine Sequence for the Assessment of Fetal Behavior in Utero

Abstract: BACKGROUND AND PURPOSE:The assessment of motor function is an essential component of neurologic examinations, which imaging studies have extended to the fetus. US assessment is hampered by a limited FOV, whereas MR imaging has the potential to be an alternative. Our objectives were to optimize a cine MR imaging sequence for capturing fetal movements and to perform a pilot analysis of the relationship between the frequency of movements and uterine spatial constrictions in healthy fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 34 publications
4
70
0
1
Order By: Relevance
“…In another study, Kikuchi et al (73) suggested limiting RF exposure to 40 minutes at whole-body SAR value of 2 W/kg and to 10 minutes at whole-body SAR value of 4 W/kg. In addition, Hayat et al (95) suggested limiting SAR to 2 W/kg in SSFP.…”
Section: Other Considerationsmentioning
confidence: 99%
“…In another study, Kikuchi et al (73) suggested limiting RF exposure to 40 minutes at whole-body SAR value of 2 W/kg and to 10 minutes at whole-body SAR value of 4 W/kg. In addition, Hayat et al (95) suggested limiting SAR to 2 W/kg in SSFP.…”
Section: Other Considerationsmentioning
confidence: 99%
“…7 Locating the ROI is successful in 81% of scans, with success being defined as no loss of foetal tissue, and a clear reduction in maternal tissue.…”
Section: Resultsmentioning
confidence: 99%
“…[16] All these movements are completed at the 15 th gestational week but mothers can feel these movements during 16 th to 18 th weeks. Hayat et al [17] reported that the frequency of the fetal movements was generally much more than the third trimester (36 th week) and if fetus has got decreased central nervous system maturity, fetal movements may hypokinesia or akinesia.…”
Section: Discussionmentioning
confidence: 99%